2023
DOI: 10.1111/bjso.12641
|View full text |Cite
|
Sign up to set email alerts
|

Does income inequality increase status anxiety? Not directly, the role of perceived upward and downward mobility

Abstract: Status anxiety theory posits that higher income inequality leads people to attribute more importance to their socioeconomic status and to worry about the position they occupy on the social ladder. We investigated through two experimental studies (N = 1117) the causal effect of economic inequality on status anxiety and whether expected upward and downward mobility mediates this effect. In Study 1, perceived economic inequality indirectly increased status anxiety through lesser expected upward mobility. In Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Future research should provide a more comprehensive investigation by including other potential mechanisms (e.g. status anxiety; Melita et al, 2023; Schmalor, 2018), which could enrich psychological theorizing on economic inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should provide a more comprehensive investigation by including other potential mechanisms (e.g. status anxiety; Melita et al, 2023; Schmalor, 2018), which could enrich psychological theorizing on economic inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The principal idea of Wilkinson and Pickett's (2009) Spirit Level Theory is that environments of high economic inequality are characterized by a normative climate of competition (see also Sánchez-Rodríguez et al, 2023). Consistent with such theorizing, empirical evidence shows that economic inequality increases tendencies for social comparison (Cheung & Lucas, 2016;Delhey et al, 2017) and the concern for a person's social standing (Melita et al, 2023;Wilkinson & Pickett, 2017). It is important to acknowledge that since its publication, the Spirit Level Theory has been criticized both on methodological and empirically grounds (e.g., Nettle, 2018;Saunders & Noble, 2010), and what remains not fully understood is when, where, and how economic inequality is perceived in the first place (see Peters & Jetten, 2023).…”
Section: Economic Inequality Harms Social Cohesion and Interpersonal ...mentioning
confidence: 97%
“…Economic inequality also heightens individuals' concerns for their standing in society and that they receive enough positive recognition from others (Layte & Whelan, 2014; Melita et al., 2021). This in turn may reduce their happiness and life satisfaction (Kawachi & Kennedy, 1999; Melita et al., 2023; Oishi et al., 2011). Unsurprisingly, under conditions of high economic inequality, individuals trust others less (Elgar & Aitken, 2011; Kawachi et al., 1997; but also see Y. Kim et al., 2022), and they use social stereotypes more (Moreno‐Bella et al., 2022).…”
Section: Economic Inequality Harms Social Cohesion and Interpersonal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,19,20 More recently, the debate has centered around the Richard Wilkinson and Kate Pickett 2010 book The Spirit Level. 21 Interest in the possible causal link between income inequality and health 22,23 remains high [24][25][26] because it has been suggested that, if causal, it may result in more than a million excess deaths per year across Organisation for Economic Co-operation and Development countries. 20 The recent rise of income inequality both in the United States 27 and the United Kingdom 28 for the first time in over a decade, and the suspected link between relative income and COVID-19 outcomes, has bolstered calls for policymakers to renew their focus on income inequality.…”
mentioning
confidence: 99%